Bioconversion of Crude Glycerol into 1,3-propanediol by an Anaerobic Mixed Microbial Consortium - Sureewan Sittijunda (Science Faculty of Chiang Mai University, 2019)
Response surface methodology with Box-Behnken design was applied to identify optimum culture compositions for 1,3-propanediol (1,3-PD) production from crude glycerol by an anaerobic mixed microbial consortium. Endo nutrient addition strongly influenced 1,3-PD production with a maximum 1,3-PD concentration of 33.72 g/dm3 achieved at 60.18 g/dm3 crude glycerol, 2.73 g/dm3 yeast extract, 205.51 mg/dm3 Na2HPO4, and 0.60 cm3/dm3 Endo nutrient. A verification experiment determined maximum concentration of 1,3-PD and glycerol consumption at 30.30 ± 9.78 g/dm3 and 70.61%, respectively, confirming the validity of the predicted model. Microbial community analysis by polymerase chain reaction-denaturing gradient gel electrophoresis revealed predominant 1,3-PD producing bacteria in the fermentation broth at optimum condition as Enterobacter sp. and Citrobacter sp.